The Youth Olympic Games in the service of protecting and promoting World Cultural Heritage - Καραλή, Μαρία (Πανεπιστήμιο Πελοποννήσου, 2012)
Singapore 2010 Closing Ceremony Speech by IOC President, Jacques Rogge Congratulations and thank you, Singapore, for a job superbly done. You rose brilliantly to the challenge of combining elite sport, modern education and culture. Throughout these 12 days, we all enjoyed the warm hospitality of the public authorities, of the very successful Organizing Committee and of the 20,000 wonderful volunteers. These Games will leave a great human legacy in Singapore and around the world. These Games were full of innovation, creativity, joy and a sharing of Olympic values. Dear athletes, you made us proud. You have learnt what it means to be a true champion, not simply a winner. You have shown us that a new generation is ready to embrace and share Olympic values. You thrilled us with your splendid performances. But, more than that, you inspired us with your enthusiasm, your spirit and the sheer joy you brought to the task of competing, learning and living with fellow athletes from around the world. These were truly inspirational games. Dear athletes, you have now earned the title Young Olympian. And when, years from now, you reflect on your sports career, you will be able to say: “I was in Singapore, where it all began.” The Youth Olympic Flame will go out tonight, but the spirit of Singapore will remain. The International Olympic Committee will continue to promote this spirit at the inaugural Winter Youth Olympic Games in Innsbruck, Austria, and at the second Summer Youth Olympic Games in Nanjing, China. You, dear athletes, will keep this Singapore Spirit alive in your countries as true role models. I now declare the inaugural Youth Olympic Games in Singapore closed, and, in accordance with tradition, I call upon the Youth of the World to assemble in four years’ time in Nanjing, China, for the second Summer Youth Olympic Games. Thank you.
Keywords: Youth Olympic Games - Singapore; Olympics - Philosophy; Παιδικοί Ολυμπιακοί Αγώνες - Σιγκαπούρη; Ολυμπιακοί αγώνες - Φιλοσοφία; Olympic values; Olympic Education; Olympic education program; World cucltural heritage